“Diseño organizacional para la asociación Agropecuaria “4 de abril” en el recinto La Josefina – cantón La Maná, año 2023. - Campaña Ronquillo, Damaris Pamela (2023)
Organizational design is a fundamental aspect of the success and survival of associations or organizations. The present degree work has as its theme: Organizational Design for the Agriculture Association "April 4th" of the La Josefina, La Maná canton, Year 2023. Its main objective is to elaborate an organizational design by determining different internal activities for each area that makes up its structure, being a fundamental tool when delegating tasks to partners. The lack of an organizational structure causes incoordination, inefficient decisions, and internal conflicts, in addition to confusing the roles and responsibilities of each member. Deductive methods used correctly deal with the current troubles in the association to propose solutions to the problems and the analytics allows the correct interpretation of the documents consulted at that time. The types of this investigation included descriptive, bibliographic research and techniques such as interviews, and surveys, and the data collection facilitated their analysis and interpretation. The Association has its infrastructure where the products are made and their deficit is due to not having an organizational structure, good communication between partners, and the support of the FEPP Group. The proposal developed a base in the organizational structure with the mission, vision, and values, a process-based management model, and employed process maps and flowcharts. As a result, an adequate structure helps to increase the efficiency and effectiveness of the activities, to benefit the growth and economic performance.